2020
DOI: 10.4012/dmj.2019-139
|View full text |Cite
|
Sign up to set email alerts
|

Bond strength and computational analysis for silane coupling treatments on the adhesion of resin block for CAD/CAM crowns

Abstract: The purposes of this study were to evaluate the shear bond strength and perform the computational analysis for silane coupling treatments on the adhesion between CAD/CAM composite resin and resin cement. As silane coupling agents, γ-methacryloyloxy propyltrimethoxysilane, 8-methacryloyloxyoctyl trimethoxysilane, and 3-methacryloyloxypropyl trichlorosilane were used. The shear bond strengths were influenced by the silane coupling agent used, its application method, and acid addition. There was no correlation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
0
8
0
3
Order By: Relevance
“…The newly developed cement contained a silane coupling monomer that has a longer carbon chain than γ-MPTS according to the manufacturer (https://www.trademarkelite.com/europe/trademark/trademark-detail/0179 96211/Chemical-Affinity-Long-Carbon-chain-Silane-Coupling-Agent-LCS), (11 November 2021), which is more hydrophobic. This monomer did not show hydrolysis when incorporated into the resin cement paste, which could explain why no difference was found in µTBS between the two types of self-adhesive resin cement in this study of [27].…”
Section: Discussionmentioning
confidence: 65%
“…The newly developed cement contained a silane coupling monomer that has a longer carbon chain than γ-MPTS according to the manufacturer (https://www.trademarkelite.com/europe/trademark/trademark-detail/0179 96211/Chemical-Affinity-Long-Carbon-chain-Silane-Coupling-Agent-LCS), (11 November 2021), which is more hydrophobic. This monomer did not show hydrolysis when incorporated into the resin cement paste, which could explain why no difference was found in µTBS between the two types of self-adhesive resin cement in this study of [27].…”
Section: Discussionmentioning
confidence: 65%
“…Use of oligomer contributes to reduce. Long organic chain type SCA such as 3‐methacroxyoctyltrimethoxysilane 34 seems to be useful for both lowering the crosslinking density of network and reducing alcohol generation. Research of SCA with mono‐ethoxy group and bulky organic chains (3‐mercaptopropyl‐ethyoxyl‐di[tridecyl‐pentamethoxy]‐silane) 35 is also done.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, all glass fiber posts were silanized, since different authors have reported that applying silane to glass fiber posts improves adhesion to cement and dentin by selectively exposing the glass fibers, unlike other treatments that can cause fractures or cracks, affecting the mechanical stability of the stump. [ 10 20 , 21 26 ] In addition, the application of silane is simple, being a widely accepted pretreatment procedure among researchers. [ 1 27 ]…”
Section: Discussionmentioning
confidence: 99%
“…Instead, silanization is the most commonly used chemical pretreatment when placing a glass fiber post, since coupling agents such as silane are bifunctional molecules in which one end is able to react with the inorganic glass fiber and the other with the organic resin of the luting agent, thus favoring good adhesion. [ 20 21 ]…”
Section: Introductionmentioning
confidence: 99%